Karakteristik sensoris krimer kental dari kacang hijau menggunakan metode uji segitiga dan hedonik - Yunda Maymanah Rahmadewi; Palupi Melati Pangastuti (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
The shift in the vegan concept into a new lifestyle trend for urban communities has led to the development of plant-based foodstuffs into several processed products. Green beans with complex nutritional content have the potential to develop into a sweet thick creamer that can be developed as a complement to bakery pastry products. The purpose of this study was to develop sweetened condensed creamer made from mung bean as an alternative to filling in milk pies, to assess whether or not there was a difference between sweet thick creamer made from mung bean and animal sweetened condensed creamer, and to assess the panelists' preference for sweetened mung bean creamer. Sweet thick creamer is made from peeled green peas with variations in the amount of added sugar as much as 35%, 40%, and 45%. The evaluation method for sweet thick creamer uses a differentiation test with the triangle test method and a preference test with the hedonic test method. The results obtained were then tested binomially with a probability of 1% for the difference test and statistically with a probability of 5% for the preference test. The results of the binomial test on the triangle test showed that the thick creamer of mung bean had different sensory attributes from the thick creamer of cow's milk. The sugar concentration which increased from 35% to 45% did not make any difference and increased the preference of the panelists on the attributes of viscosity, color, taste, aroma, and overall preference for sweet thick creamer of mung bean. The conclusion obtained is that the sweetened thick creamer of mung bean has different attributes of thickness, color, sweetness, and aroma compared to the sweetened condensed creamer of cow's milk. The use of sugar with different concentrations did not give a significant difference to the preferences of the panelists on the attributes of thickness, color, taste, aroma, and overall preference for sweetened mung bean creamer.